Convergence Theorems for a Finite Family of l-Asymptotically Nonexpansive Mappings in Banach Spaces - Birol Gunduz (Science Faculty of Chiang Mai University, 2019)
In this paper, a new two-step iterative scheme for a finite family of Ii-asymptocally nonexpansive mappings TiNi=1 is constructed in a uniformly convex Banach space. Weak and strong convergence theorems of this iterative scheme to a common fixed point of TiNi=1 and IiNi=1 are proved in a uniformly convex Banach space.